1992
DOI: 10.1101/gr.2.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch amplification mutation assay (MAMA): application to the c-H-ras gene.

Abstract: We have found that under appropriate conditions, an allele-specific polymerase chain reaction (PCR) can achieve a sensitivity suitable for measuring specific, infrequent mutations in single cell systems or in animal tissues. Using the 12th codon GC-to-AT mutation in the rat c-Ha-ras gene as a model system, we have defined conditions that allow for measurement of mutations present at frequencies as low as one in 10(5) gene copies. Our approach involved the use of PCR primers that created a single mismatch with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
262
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 356 publications
(267 citation statements)
references
References 19 publications
2
262
0
Order By: Relevance
“…Detection levels of mutant ras sequences present at as low as 1 in 105 wild-type sequences have been reported (Ehlen and Dubeau, 1989;Cha et al, 1992) and 1 in 103 (this study and Carpenter et al, 1996). This ability of the technique to detect rare mutations in a background of normal DNA demonstrates its potential role in screening or in the monitoring of residual disease.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Detection levels of mutant ras sequences present at as low as 1 in 105 wild-type sequences have been reported (Ehlen and Dubeau, 1989;Cha et al, 1992) and 1 in 103 (this study and Carpenter et al, 1996). This ability of the technique to detect rare mutations in a background of normal DNA demonstrates its potential role in screening or in the monitoring of residual disease.…”
Section: Discussionsupporting
confidence: 55%
“…In fact, control reactions for tumour DNA analysis had routinely lower ratios of mutant to wild-type input DNA. Other groups (Ehlen and Dubeau, 1989;Stork et al, 1991;Cha et al, 1992;Hasegawa et al, 1995;Hayashi et al, 1995;Carpenter et al, 1996) have reported tests based on the same principles as the ARMS tests described here.…”
Section: Discussionmentioning
confidence: 74%
“…Probes speci®c for each point mutation can interfere with one another during hybridization or polymerase extension. Thus, while allele-speci®c PCR can detect individual point mutations, it is not e ective for multiplex detection of all possible K-ras mutations in a homogeneous assay (Cha et al, 1992;Hasegawa et al, 1995;Hayashi et al, 1994Hayashi et al, , 1995Losi et al, 1992;Tada et al, 1993;Wu et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Several PCR based techniques can detect single-base mutations present in a minority population of human tumor cells: allele-speci®c PCR (AS-PCR), which includes MASA, PASA, MS-PCR, MAMA or ARMS ampli®cation (Cha et al, 1992;Chehab and Kan, 1989;Hasegawa et al, 1995;Hayashi et al, 1994Hayashi et al, , 1995Kwok et al, 1990;Li et al, 1990;Lo et al, 1991;Mansfeld and Bos, 1992;Orita et al, 1989;Ruano and Kidd, 1989;Rust et al, 1993;Seyama et al, 1992;Tada et al, 1993;Wu et al, 1989) as well as by primer mediated RFLP (Chen and Viola, 1991;Di Giuseppe et al, 1994;Kahn et al, 1991;Levi et al, 1991;Mitsudomi et al, 1991) or electrophoretic mobilitybased methods (Chen and Thilly, 1994;Fodde and Losekoot, 1994;Khrapko et al, 1994). However, these ampli®cation methods are susceptible to false-positive signals due to mis-extension of the mutant-speci®c primer on wild-type target.…”
Section: Use Of Multiplex Pcr/ldr To Detect Mutations In Nonmicrodissmentioning
confidence: 99%
See 1 more Smart Citation